SIM Samples Investigation by Statistical Methods - Várallyay, László; Kovács, Béla; Prokisch, József; Szegvári, Ildikó (Acta Agraria Debreceniensis, 2003)
The assessment of the present condition of the soil is very important, because the accession of the number of the European Union members is in the near future. This can be the base of the modern agrarian environmental management programme. The assessment must be objective, detailed and analyse the processes in the soil.Respecting the above causes was decided to create an Environmental Information Monitoring System. This system consists of more parts. One of them is the Soil Information Monitoring System (SIM). This system started to work in 1992.This system has two functions. Creating and actuation is obligatory from the international contracts, on the other hand the public SIM has very important role in the conservation of the soil.The SIM territorial measuring grid consists of 1236 measuring points. These points are representatives. The distributions of the points by the types of soil attend the variety of the types of soil of the country.The investigated elements in 6 types of soil were in our experiment (the group of scandium and the lanthanide series elements). There are 6 elements above the detection limit (Gadolinium, Neodymium, Praseodymium, Scandium, Samarium, Yttrium).The Neodymium concentration is 2 times higher than the content of Gadolinium and Yttrium.The Neodymium concentration is 4 times higher than the content of Praseodymium, Scandium and Samarium.In the case of Dysprosium, Europium, Lutetium, Terbium, Ytterbium the concentrations were below 1 mg/kg.